2014
DOI: 10.1016/j.polymer.2013.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Main-chain polybenzoxazine nanofibers via electrospinning

Abstract: a b s t r a c tHere we report the successful production of nanofibers from main-chain polybenzoxazines (MCPBz) via electrospinning without using any other carrier polymer matrix. Two different types of MCPBz (PBA-ad6 and PBA-ad12) were synthesized by using two types of difunctional amine (1,6-diaminohexane and 1,12-diaminododecane), bisphenol-A, and paraformaldehyde as starting materials through a Mannich reaction.1 H NMR and FTIR spectroscopy studies have confirmed the chemical structures of the two MCPBz.We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…First example of the cross-linking of polybenzoxazine-based nanofibers by directly thermal curing was given by Li and co-workers [29]. Initially, they produced nanofibers from MCPBz synthesized by using 4,4 0 -diaminophenylether and bisphenol-A, and then they were able to obtain cross-linked MCPBz nanofibers by thermal curing at 240 C for 3 h. On the contrary, our previous study demonstrated that nanofibers produced by MCPBz which based on the bisphenol-A and diamines with long aliphatic chains (1,12diaminododecane and 1,6-diaminohexane) have not shown resistance to the heat treatment during the thermal curing and nanofibers lost the fiber morphology at low temperatures around 75e100 C [28]. Presumably, 4,4 0 -diaminophenylether provided more rigid structure to the MCPBz nanofibers compared with 1,12diaminododecane and 1,6-diaminohexane, hence, the melting temperature of the nanofibers obtained from the former one is much higher than the others.…”
Section: Curing Studies Of Dhbp-ad6 and Dhbp-ad12 Nanofibersmentioning
confidence: 89%
See 1 more Smart Citation
“…First example of the cross-linking of polybenzoxazine-based nanofibers by directly thermal curing was given by Li and co-workers [29]. Initially, they produced nanofibers from MCPBz synthesized by using 4,4 0 -diaminophenylether and bisphenol-A, and then they were able to obtain cross-linked MCPBz nanofibers by thermal curing at 240 C for 3 h. On the contrary, our previous study demonstrated that nanofibers produced by MCPBz which based on the bisphenol-A and diamines with long aliphatic chains (1,12diaminododecane and 1,6-diaminohexane) have not shown resistance to the heat treatment during the thermal curing and nanofibers lost the fiber morphology at low temperatures around 75e100 C [28]. Presumably, 4,4 0 -diaminophenylether provided more rigid structure to the MCPBz nanofibers compared with 1,12diaminododecane and 1,6-diaminohexane, hence, the melting temperature of the nanofibers obtained from the former one is much higher than the others.…”
Section: Curing Studies Of Dhbp-ad6 and Dhbp-ad12 Nanofibersmentioning
confidence: 89%
“…for various applications. On the other hand, electrospinning of nanofibers from polybenzoxazine resins is a new concept and electrospinning of MCPBz resins without using additional polymeric matrices was first reported recently by our group [28].…”
Section: Introductionmentioning
confidence: 99%
“…Ertas and Uyar reported the first study to produce bead-free and uniform polybenzoxazine nanofibers from MCPBz without using carrier polymeric matrices [75]. Initially, two different types of MCPBz (poly(BA-dh) main and poly(BA-dd) main ) were synthesized by using two types of difunctional amine (1,6-diaminohexane and 1,12diaminododecane), BA, and paraformaldehyde as starting materials through a Mannich reaction.…”
Section: Main-chain Nanofibers Obtained Without Blending With Other Pmentioning
confidence: 99%
“…Representative SEM images and corresponding fiber diameter distributions with average fiber diameter (AFD) of the electrospun nanofibers obtained from solutions of poly(BA-dh) main (A, B) 30%, (C, D) 35%, (E, F) 40%, and (G, H) 45%. Inset shows magnified view of a typical region[75].FIG. 22 Representative SEM images and corresponding fiber diameter distributions of the electrospun nanofibers obtained from solutions of poly(BA-dd) main (A, B) 15%, (C, D) 18%, and (E, F) 20%.…”
mentioning
confidence: 99%
“…These properties enable the production of high‐performance composite materials . Thus, immense research has been conducted on different forms of polybenzoxazines including bulk, film, aerogel, membrane, and nanofibers . However, far too little attention has been paid to the incorporation of polybenzoxazine into polymeric nanofibers …”
Section: Introductionmentioning
confidence: 99%